The Relationship between Family Support and Adherence to Taking Medication in Hypertension Patients at the Internal Medicine Polyclinic - Hafiza Usnaini; Fransisca Anjar Rina Setyani; Scholastika Fina Aryu P (Lentera Perawat, 2025)
Hypertension is a non-communicable disease and is still referred to as a silent killer because its symptoms are difficult to recognise and often there are no symptoms or no symptoms at all. Family support is one of the most important types of support with the aim of achieving optimal medication adherence. Family support can be provided in the form of emotional, appreciative, instrumental and informational support. This study aims to analyse the relationship between family support and adherence to taking medication in patients with hypertension at the Internal Medicine Poly of Santo Antonio Hospital Baturaja. This research is a type of quantitative research with a cross sectional design. The population in this study were 73 people with hypertension in the Internal Medicine Clinic of Santo Antonio Hospital. In this study, the sample was hypertensive patients in the Internal Medicine Clinic of Santo Antonio Hospital Baturaja using accidental sampling as many as 62 people according to the inclusion criteria. The instruments used in this study were the family support questionnaire and the Morisky Medication Adherence Scales-8 (MMAS-8) instrument. The results of this study obtained the distribution of family support for hypertensive patients at the Internal Medicine Clinic of Santo Antonio Hospital with good family support, namely 39 (62.9%) and a moderate level of compliance as many as 28 people (45.2%). The results of statistical analysis using the spearman test showed a significant relationship between family support and adherence to taking medication in patients with hypertension in the Internal Medicine Poly of Santo Antonio Hospital Baturaja (pvalue = 0.000). This study can be an input for nurses to be able to continue to educate hypertensive patients to continue taking medication regularly considering that family support can affect adherence to taking medication.